Financial hedging - Catlere, Patrick N. (Nova Science Publishers, 2009)
The problem of credit risk is an important problem in finance. It consists of computing the probability of a firm defaulting on a debt. The time evolution of rating for credit risk models can be studied by means of Markov transition models. This book looks at the homogeneous and non-homogeneous semi-Markov backward credit risk migration models.